A Portrait of Remedial Instruction: Faculty Workload and Assessment Techniques - Boyer, Patricia Grace; Butner, Bonita K.; Smith, Dwyane (Higher Education, 2007)
Remediation in postsecondary education continues to be an issue that is hotly debated by institutional leaders and state policymakers. The National Center for Education Statistics [The National Center for Education Statistics. (2003). Remedial education at higher education institutions in fall 2000. PEQIS. Washington, D.C.: U.S. Department of Education.] estimates that 98% of public 2-year and 80% of public 4-year institutions offered at least one remedial course. The need for remedial courses is also demonstrated by the growing number of students who enroll each year. Studies that examine students and placement are found in the literature, but few examine the faculty who teach in remedial programs [Boylan, H., Bonham, B. S., Jackson, J., & Saxon, D. P. (1995). Research in Developmental Education, 12(1), 42–52.]. The purpose of this study was to examine faculty who teach remedial courses. In particular, we were interested in faculty workload and the assessment techniques employed by faculty based upon type and level of institution. More specifically, data was analyzed using the NSOPF: 99 database on faculty at 2-year and 4-year institutions as well as faculty at private and public institutions. Some comparisons between faculty teaching remedial courses and nonremedial courses are presented.
Keywords: Assessment techniques; Faculty workload; Institutional type; NSOPF: 99; Remediation; dept.pres; peer-reviewed

Beginning Racquetball - Norton, Cheryl; Bryant, James E. (Wadsworth activities series, 2004)
Keywords: Handbooks, manuals, etc; Racquetball; dept.pres; faculty_collection

Beginning Racquetball - Norton, Cheryl; Bryant, James E. (Wadsworth/Thomson Learning, 2001)
Keywords: Handbooks, manuals, etc; Racquetball; dept.pres; faculty_collection

The History of AAIE in Two Parts. - Engleman, Finis Ewing; Rushton, Edward W.; Brody, Leonard Harry; Brown, Gilbert C.; Association for the Advancement of International Education (The Association for the Advancement of International Education, 1990)
Keywords: Association for the Advancement of International Education; History; International education; dept.pres; faculty_collection

Racquetball: A Primer - Norton, Cheryl; Bryant, James E. (Morton, 1986)
Keywords: Racquetball; dept.pres; faculty_collection

The Relation of Selected Organizational Variables to the Perceived Role Performance of Professional-Technical Researchers - Harrison, E. Frank (University Microfilms, 1984)
Keywords: Management; Research; dept.pres; faculty_collection

The Managerial Decision-Making Process - Harrison, E. Frank (Houghton Mifflin, 1981)
Keywords: Decision making; dept.pres; faculty_collection

Management and Organizations - Harrison, E. Frank (Houghton Mifflin, 1978)
Keywords: Management; Organization; dept.pres; faculty_collection

The Pleasure Was Mine - Engleman, Finis Ewing (Interstate Printers & Publishers, 1971)
Keywords: Engleman, Finis Ewing, 1895-; Education; History; United States; dept.pres; faculty_collection

The Consent of the Governed - Engleman, Finis Ewing (Baldwin lectures, 1963)
Keywords: Education; United States; dept.pres; faculty_collection

The Development of the Modern Problems Course in the Senior High School. - Jennings, Manson Van Buren (Contributions to education ; no. 968, 1950)
Keywords: Social problems; Study and teaching; dept.pres; faculty_collection

Charter of King Charles II of England and William Penn's Frames of Government for Pennsylvania, Including Historical Notes on William Penn, Founder, Master Builder, and Statesman. - Pennsylvania Department of Public Instruction (Dunlap printing company, 1939)
Keywords: Colonial period, ca. 1600-1775; History; Penn, William, 1644-1718; Pennsylvania; dept.pres; faculty_collection

Scales and Fins - Engleman, Finis Ewing (D.C. Heath and Co., 1938)
Keywords: Fisheries; Fishes; Fishing; dept.pres; faculty_collection

Lectures on Psychology for Teachers - Morrill, Arthur B. (Harty-Musch Press, 1916)
Keywords: Educational psychology; dept.pres; faculty_collection

The Sacred and Profane in English Renaissance Literature - Papazian, Mary Arshagouni (University of Delaware Press, 2008)
"This collection of thirteen original essays focuses squarely on the question of how properly to define the intersection between the sacred and profane in early modern English literature. Growing out of the work of church historians of the previous decade, and the renewed interest in our own time in questions of how the religious and secular realms overlap and (re)define each other, the contributors to this volume focus their attention on defining anew the tension between the sacred and profane in this period. Fundamental to this reframing is a strong belief among all contributors that the sacred and profane must be defined in relation to each other. Thus, the essays in this volume seek to advance more nuanced approaches to these issues that enable us to move beyond simplistic categories whereby the sacred and profane - and sacred and profane literature - occupied several different spheres, were produced by different writers, and spoke to different audiences."--Jacket.
Keywords: 16th century; 16th century; Holy, The, in literature; Secularism in literature; Sacred space in literature; Civilization, Secular; Renaissance; 17th century; Great Britain; 17th century; Religion and literature; Early modern, 1500-1700; England; Christian literature, English; English literature; Great Britain; History; History and criticism; Devotional literature, English; History and criticism; Great Britain; History and criticism; Religion and literature; Intellectual life; dept.pres; faculty_collection; unidentified

John Donne and the Protestant Reformation New Perspectives - Papazian, Mary Arshagouni (Wayne State University Press, 2003)
"This collection includes thirteen essays that together place Donne broadly in the context of English and European traditions and explore his divine poetry, his prose work, the Devotions Upon Emergent Occassions, and his sermons. It becomes clear that in adopting the values of the Reformation, Donne does not completely reject everything from his Catholic background. Rather, the clash of religion erupts in his work in both moving and disconcerting ways." "This collection offers a fresh understanding of Donne's hard-won irenicism, which he achieved at great personal and professional risk."--Jacket.
Keywords: 17th century; Christian literature, English; 17th century; Protestantism and literature; Donne, John, 1572-1631; England; History; History and criticism; Reformation; Religion; Christianity and literature; dept.pres; faculty_collection